A combined flow cell–respiration box to quantify carbon transformation processes in undisturbed soil. Issue 1 (9th November 2021) - Redweik, Henrik; Rahlfs, Moritz; Bachmann, Jörg
Abstract: A new experimental laboratory design is introduced to analyze and quantify transport and turnover processes in top‐ and subsoils. The proposed technique allows the monitoring of transformation processes in an undisturbed soil matrix while preserving entirely intact soil particle interfaces. The experimental setup with undisturbed soil samples, which are embedded into two coupled gas sealed chambers, allows on‐time measurement of soil respiration processes under realistic moisture, water flux, and temperature conditions. Core Ideas: We introduce improved column breakthrough experiments with the advantage of visual monitoring processes. The stated device combines laboratory precision and controllability with field conditions such as temperature regime. Due to its design, it is possible to combine soil horizons, which allows us to simulate soil profiles. In combination with labeled C, small‐scale mass balancing of the C cycle is possible. The controllability allows flow in unsaturated conditions with control over water content and flow velocity column breakthrough experiments with the advantage of visual monitoring processes.